Comparison of the TIP4P-2005, SWM4-DP and BK3 interaction potentials of liquid water with respect to their consistency with neutron and X-ray diffraction data of pure water - Steinczinger, Z.; Pusztai, L. (Condensed Matter Physics, 2013)
Following a fairly comprehensive study on popular interaction potentials of water (Pusztai et al 2008, J. Chem. Phys., 129, 184103), here two more recent, polarizable potential sets, SWM4-DP (Lamoureux et al., Chem. Phys. Lett., 2006, 418, 245) and BK3 (Kiss et al. J. Chem. Phys., 2013, 138, 204507) are compared to the TIP4P-2005 water potential (Abascal et al., J. Chem. Phys., 2005, 123, 234505) that had appeared the most favoravble previously. The basis of comparison was the compatibility with results of neutron and X-ray diffraction experiments on pure water, using the scheme applied by Pusztai et al. (2008). The scheme combines the experimental total scattering structure factors (TSSF) and partial radial distribution functions (PRDF) from molecular dynamics simulations in a single structural model. Goodness-of-fit values to the O-O, O-H and H-H simulated PRDF-s and to the experimental neutron and X-ray TSSF provided a measure that can characterize the level of consistency between interaction potentials and diffraction experiments. Among the sets of partial RDF-s investigated here, the ones corresponding to the SWM4-DP potential parameters have proven to be the most consistent with the particular diffraction results taken for the present study, by a hardly significant margin ahead of BK3. Perhaps more importantly, it is shown that the three sets of potential parameters produce nearly equivalent PRDF-s that may all be made consistent with diffraction data at a very high level. The largest differences can be detected in terms of the O-O partial radial distribution function.